Substitution of paper for sucrose can reverse apparent male sterility in Neurospora - A. Fairfield; B. C. Turner (Fungal Genetics Reports, 1993)
For many years we ascertained the species of newly collected Neurospora cultures by using them to fertilize standard species testers which had grown for five days on crossing medium with sucrose as the carbon source.